?m-Statistical convergence - Et, M; Nuray, F (Indian Nat Sci Acad, 2001)
In this paper, we define a general sequence space Delta (m) (X) = {x = (x(k)) : (Delta (m) x(k)) is an element of X}, (m is an element of N), where X is any sequence space. We establish some inclusion relations, topological results and we characterize the continuous duals of Delta (m) (X). Furthermore we introduce of Delta (m)-statistical convergence and given inclusion relation between Delta (m) (w(p))-convergence and Delta (m)-statistically convergence, The results are more general than those of Kizmaz [3], Fridy [6], Conor [7], Basarir [8], Et-Colak [9] and Salat [10].